COVID-19 in rheumatoid arthritis cases: an Iranian referral center experience - Shadmanfar, Soraya (Clin Rheumatol, 2020)
Coronavirus infections, known as COVID-19, can induce a fatal respiratory system infection and also affect other organs, such as the kidney and heart. The mortality rate has been estimated between 1 and 5% in previous reports; however, the mortality and morbidity can be higher in patients with the immune-deficiency condition. Rheumatoid arthritis (RA) is one of the most rheumatoid disorders, and it is important to report their clinical and paraclinical data when affected with COVID-19. Evidence about their laboratory and radiologic findings is limited. In this case series, 10 cases of chronic and approved rheumatoid arthritis (RA) affected by COVID-19 are presented. Only 40% had dry cough, but myalgia and weakness as the general first presentation of infections was reported in most cases (80%). Gastrointestinal symptoms, including nausea/vomiting, diarrhea, anorexia, and abdominal pain, were reported in 50% of individuals. In blood cell count, 30% of cases had thrombocytopenia, and ESR in all cases was positive. Abnormal CRP and elevated LDH were seen in 90% of cases. In HRCT assessment, all cases had an abnormal parenchymal pattern, and 90% of cases presented the usual pattern of COVID-19 (bilateral multifocal GGO/consolidation). Although it is a limited report, these findings are helpful for comparison of clinical and paraclinical cases in RA cases with normal cases.